The Gold Can Stay: The Meaning Transformation of The Word ‘Gold’ In Robert Frost’s Nothing Gold Can Stay And S.E Hinton’s The Outsiders - Anne Lisa Pertiwi (Vivid: Journal of Language and Literature, 2018)
This thesis discusses the meaning transformation of the word ‘gold’ from ‘’Nothing Gold Can Stay’’ by Robert Frost to the phrase ‘stay gold’ in The Outsiders which give the big impact to the characters’ life in the novel. This research was conducted by explaining the theme of the poem and the novel referring to New Criticism theory to uncover the meaning transformation of the word ‘gold’ in each work. From the result of this analysis, the author finds that the meaning of ‘’Nothing Gold Can Stay’’ is pessimistic and materialistic notions while the phrase ‘stay gold’ in The Outsiders which is taken from that poem shows opposite message. This phrase has spiritualistic and optimistic spirits. Then, the changing meaning of this phrase successfully drive the main character, Ponyboy Curtis, becomes better person.